2018
DOI: 10.1002/cncr.31310
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell–depleted haploidentical stem cell transplantation results improve with time in adults with acute leukemia: A study from the Acute Leukemia Working Party of the European Society of Blood and Marrow Transplantation (EBMT)

Abstract: The outcome of patients with acute leukemia who underwent T-cell-depleted haplo has improved over time. Cancer 2018;124:2142-50. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
2
5
0
2
Order By: Relevance
“…61, 62) compared with early T-cell-depleted haplo-HSCT procedures (30%-54%; refs. 21,26,33). Especially among patients ages 40-60 years, the rate of NRM did not increase with age following myeloablative conditioning, which is in accordance with our previous report that the outcomes of older patients (age > 50 years) were comparable with those of younger patients (63).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…61, 62) compared with early T-cell-depleted haplo-HSCT procedures (30%-54%; refs. 21,26,33). Especially among patients ages 40-60 years, the rate of NRM did not increase with age following myeloablative conditioning, which is in accordance with our previous report that the outcomes of older patients (age > 50 years) were comparable with those of younger patients (63).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the impact of imbalanced patient characteristics, such as the lower median age in the haplo-HSCT cohort than in the chemotherapy group, likely affected the observed outcomes. Thus, whether the benefit of haplo-HSCT in individuals with heterogeneous AML can be replicated for those with int-risk AML remains controversial (31,33).…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of a low CIR and an acceptable NRM resulted in promising results of haplo-SCT in the present study, which were comparable to those in previous reports (5year LFS 68.7%, OS 70.1%) [5,8]. As NRM of haplo-SCT has generally improved with either the PT-CY (7 to 23%) or ATG+G-CSF protocol (11-13%) compared with early procedures [4,9,10], NRM might no longer be a limiting factor of receiving haplo-SCT, especially in experienced centers. haplo-SCT was associated with lower CIR in both the Con-1 MRD +/− subgroups in the current study; meanwhile, cautions must be taken as CIR of non-SCT cohort might be higher compared with previous reports (46-49%) [1,2].…”
Section: To the Editorsupporting
confidence: 88%
“…Haplo-HSCT is an attractive treatment for patients with high-risk hematological malignancies lacking a well-matched unrelated donor and who require a HSCT urgently. Today, rejection and GvHD are no longer major issues and a recent registry-based study of the EBMT confirmed that outcomes of TCD haplo-HSCT have improved over time reflecting gaining experience, better selection of the donor-recipient pairs, evolution of the conditioning regimens, better supportive care, and treatment options for infections complications, that remain the main cause of death in this setting (84).…”
Section: Discussionmentioning
confidence: 99%